DINAMIKA DIPLOMASI BENCANA MELALUI PENDEKATAN PARADIPLOMASI OLEH PEMERINTAH DAERAH SULAWESI SELATAN - Andi Amytia Resty (UNIDA Gontor, 2018)
One of the disaster problems in South Sulawesi region is the atti-tude of non-responsive disaster from the local community caused by the disaster that happened still in small scale. Whereas the disaster happened continuously causing big loss for local government. Therefore, one of the government’s efforts to overcome the problem by establishing cooperation through paradiplomacy approach with the Australian government, both of which have similar patterns of disaster. This research uses descriptive qualitative method to describe the facts of cooperation by applying the the-ory of disaster diplomacy and paradiplomacy. While data collection tech-niques used through library research and in-depth interview both from the local government of South Sulawesi and the Australian government. The results of this study illustrate that the cooperation undertaken by the local government of South Sulawesi and Australia runs smoothly. Through the cooperation, the local government of South Sulawesi gained new knowl-edge on disaster issues both pre-disaster and post-disaster. This has impli-cations for the opening of cooperation opportunities in investment in the sector of regional infrastructure and energy sector.